2018
DOI: 10.1094/pdis-01-18-0197-re
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of QoI-Resistant Phytophthora capsici Causing Pepper Phytophthora Blight in China

Abstract: Phytophthora capsici is a highly destructive plant pathogen that has spread worldwide. To date, the quinone outside inhibitor (QoI) azoxystrobin has been the choice of farmers for managing this oomycete. In this study, the sensitivity of 90 P. capsici isolates collected from Yunnan, Fujian, Jiangxi, Zhejiang, and Guangdong in southern China to azoxystrobin was assessed based on mycelial growth, sporangia formation, and zoospore discharge. Furthermore, the mitochondrial cytochrome b (cytb) gene from azoxystrobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 35 publications
1
12
0
2
Order By: Relevance
“…are the most commonly used fungicides (). However, many fungicides against oomycetes have generated serious resistance problems because of unreasonable and frequent applications in fields. Therefore, it is urgently required to develop new environmentally friendly oomycete inhibitors with high activity.…”
Section: Introductionmentioning
confidence: 99%
“…are the most commonly used fungicides (). However, many fungicides against oomycetes have generated serious resistance problems because of unreasonable and frequent applications in fields. Therefore, it is urgently required to develop new environmentally friendly oomycete inhibitors with high activity.…”
Section: Introductionmentioning
confidence: 99%
“…Another experiment on managing P. sojae on soybean using pyraclostrobin as seed treatment showed efficacy for increased chlorophyll level, shoot and root length, root activity, and continuous positive effect on enhancing the plant defense (Li et al, 2020). In contrast, some studies showed decreased sensitivity of P. capsici causing Phytophthora blight in pepper against quinone-outside inhibitor (QoI) fungicides including pyraclostrobin (Ma et al, 2018), suggesting the necessity of using fungicides in rotation to save crops from increased resistance. gens (La Spada et al, 2020), but in our study the combined application of water-soluble nitrogen, soluble potash, and T. harzianum Rifai strain T-22 1 T. virens strain G-41 was effective, which might be due to the synergistic effect of both fertilizer and biofungicide.…”
Section: Discussionmentioning
confidence: 99%
“…Both harmful and beneficial bacteria and fungi need to be considered, especially with regard to how they communicate with plant hosts, such as providing biological nutrient sources or suppressing the host’s immune response ( Zhu et al., 2018 ). Endophytes are similar to pathogens, having the ability to enter the host tissue and stay there without causing harm to the host and even being beneficial ( Ma et al., 2018a ). Both partner plants and microorganisms, such as fungi, benefit from the relationship: mycorrhizal fungi improve the nutrient status of their host plants, influencing mineral nutrition, water absorption, growth and disease resistance, whereas in exchange, the host plant is necessary for fungal growth and reproduction ( Bonfante and Genre, 2010 ).…”
Section: Identification Of Microorganisms By High-throughput Methodsmentioning
confidence: 99%